Bioresorbable scaffolds vs. drug-eluting stents for patients with myocardial infarction: A systematic review and meta-analysis of randomized clinical trials - Liu, Yong; Xiao, Di; Wu, Yang; Li, Meng; Liu, Jia; Zhuang, Rui; Ma, Liyong; Li, Jingen; Zhang, Lijing (Frontiers in Cardiovascular Medicine, 2022)
Objective To compare the efficacy and safety of bioresorbable scaffolds (BRS) with drug-eluting stents (DES) in patients with myocardial infarction undergoing percutaneous coronary interventions (PCI). Methods We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing BRS with DES on clinical outcomes with at least 12 months follow-up. Electronic databases of PubMed, CENTRAL, EMBASE, and Web of Science from inception to 1 March 2022 were systematically searched to identify relevant studies. The primary outcome of this study was the device-oriented composite endpoint (DOCE) consisting of cardiac death, target-vessel myocardial infarction, and target lesion revascularization. Secondary outcomes were a composite of major adverse cardiac events (MACE, all-cause death, target-vessel myocardial infarction, or target vessel revascularization) and the patient-oriented composite endpoint (POCE, defined as a composite of all-cause death, myocardial infarction, or revascularization). The safety outcomes were definite/probable device thrombosis and adverse events. Results Four randomized clinical trials including 803 participants with a mean age of 60.5 ± 10.8 years were included in this analysis. Patients treated with BRS had a higher risk of the DOCE (RR 1.62, 95% CI: 1.02–2.57, P = 0.04) and MACE (RR 1.77, 95% CI: 1.02–3.08, P = 0.04) compared with patients treated with DES. No significant difference on the POCE (RR 1.33, 95% CI: 0.89–1.98, P = 0.16) and the definite/probable device thrombosis (RR 1.31, 95% CI: 0.46–3.77, P = 0.61) were observed between BRS and DES. No treatment-related serious adverse events were reported. Conclusion BRS was associated with a higher risk of DOCE and MACE compared with DES in patients undergoing PCI for myocardial infarction. Although this seems less effective in preventing DOCE, BRS appears as safe as DES. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=321501], identifier [CRD 42022321501].